Human Schwann Cell Transplantation for Spinal Cord Injury: Prospects and Challenges in Translational Medicine - Monje, Paula V.; Deng, Lingxiao; Xu, Xiao-Ming (Frontiers in Cellular Neuroscience, 2021)
The benefits of transplanting cultured Schwann cells (SCs) for the treatment of spinal cord injury (SCI) have been systematically investigated in experimental animals since the early 1990s. Importantly, human SC (hSC) transplantation for SCI has advanced to clinical testing and safety has been established via clinical trials conducted in the USA and abroad. However, multiple barriers must be overcome to enable accessible and effective treatments for SCI patients. This review presents available information on hSC transplantation for SCI with the intention to uncover gaps in our knowledge and discuss areas for future development. To this end, we introduce the historical progression of the work that supports existing and prospective clinical initiatives and explain the reasons for the choice of hSCs while also addressing their limitations as cell therapy products. A search of the relevant literature revealed that rat SCs have served as a preclinical model of reference since the onset of investigations, and that hSC transplants are relatively understudied, possibly due to the sophisticated resources and expertise needed for the traditional processing of hSC cultures from human nerves. In turn, we reason that additional experimentation and a reexamination of the available data are needed to understand the therapeutic value of hSC transplants taking into consideration that the manufacturing of the hSCs themselves may require further development for extended uses in basic research and clinical settings.